2022
DOI: 10.1007/s11695-022-06266-8
|View full text |Cite
|
Sign up to set email alerts
|

Revisional Roux-en-Y Gastric Bypass Versus Revisional One-Anastomosis Gastric Bypass After Failed Sleeve Gastrectomy: a Randomized Controlled Trial

Abstract: Background High rates of revision surgery have been reported for laparoscopic sleeve gastrectomy (LSG), with weight regain (WR) as the most frequently reported cause. Roux-en-Y gastric bypass (RYGB) is the most commonly performed revision procedure, whereas one-anastomosis gastric bypass (OAGB) is a less popular approach. Methods A single-blinded randomized controlled trial was conducted. One hundred seventy-six patients were enrolled and randomized. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…Previous studies showed that weight regain after BS were associated with diabetes progression and decline in quality of life [ 21 ], so the results of this study indicating weight regain may be clinically important and should be noticed. This is similar to findings of other studies [ 30 33 ]; in study by Himpens et al [ 31 ] weight regain was appeared in 75.6% of SG patients after the sixth post-operative year. In this study, the weight gain of patients who received only SG was higher than that of patients who also had duodenal switch in addition to SG, so it seems that long-term outcome of obesity surgery depend on techniques performed.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that weight regain after BS were associated with diabetes progression and decline in quality of life [ 21 ], so the results of this study indicating weight regain may be clinically important and should be noticed. This is similar to findings of other studies [ 30 33 ]; in study by Himpens et al [ 31 ] weight regain was appeared in 75.6% of SG patients after the sixth post-operative year. In this study, the weight gain of patients who received only SG was higher than that of patients who also had duodenal switch in addition to SG, so it seems that long-term outcome of obesity surgery depend on techniques performed.…”
Section: Discussionsupporting
confidence: 92%
“…In a 2014 systematic review, RYGB after LSG, and other surgical interventions performed after LSG was reported to achieve a %EWL of 60 and 48 % over 12 and 24 months, respectively [ 32 ]. Moreover, a 2022 randomized controlled trial reported that revisional RYGB and one-anastomosis gastric bypass had comparable significant weight loss effects after failed LSG with % excessive BMI loss of 89.3±15.4 and 84.8±18.2%, respectively, after two years; both procedures were safe with no significant differences in complications and nutritional deficits [ 33 ]. Multiple systematic reviews and studies that tested alternative revision surgeries after (failed)-LSG confirmed the same result [ 31 , 34 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high rates of LSG and the high rates of subsequent conversional would result in a considerably large volume of conversional procedures after LSG, raising attention to identifying the best conversional option with the best outcomes—studies of the safety and efficacy of different conversional options after LSG would be of value to decision-makers. RYGB is the most commonly reported conversional procedure after LSG, while other commonly reported conversional procedures than RYGB for SWL after LSG include re-sleeve, biliopancreatic diversion with duodenal switch (BPD-DS), single anastomosis duodenal-ileal bypass (SADI-S), and, less commonly, one-anastomosis gastric bypass (OAGB) [ 2 , 6 9 , 12 ]. Roux-en-Y gastric bypass (RYGB) as a conversional procedure has credible outcomes regarding weight loss, relief of GERD, and nutritional deficiencies [ 2 , 6 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…RYGB is the most commonly reported conversional procedure after LSG, while other commonly reported conversional procedures than RYGB for SWL after LSG include re-sleeve, biliopancreatic diversion with duodenal switch (BPD-DS), single anastomosis duodenal-ileal bypass (SADI-S), and, less commonly, one-anastomosis gastric bypass (OAGB) [ 2 , 6 9 , 12 ]. Roux-en-Y gastric bypass (RYGB) as a conversional procedure has credible outcomes regarding weight loss, relief of GERD, and nutritional deficiencies [ 2 , 6 9 , 12 ]. The available literature includes multiple studies that have examined and compared the outcomes of various conversional procedures following LSG [ 2 , 6 , 9 , 12 , 13 ]; However, some studies have evaluated the results of conversional RYGB after LSG without making direct comparisons to alternative procedures [ 5 , 7 , 8 , 10 , 14 16 ], Furthermore, some studies have conducted comparisons between primary RYGB (PRYGB) cohorts and different cohorts of conversional RYGB following various types of previous operations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%